The empowerment in oneself to the committee of student association: A way to development with extracurricular activity - Pitaksongkram, Penphan (Academic Journal of Thailand National Sports University, 2018)
The modification in the 21st century affects the educational systematization of college education to change the extracurricular activities to be the activities which fall outside the realm of the normal curriculum of college education, will be performed by students and exist for all students. These activities can help the 21st century students gaining the skill development by themselves. They can learn from doing the real thing with their team. Using the leadership and followership then considering what they learn from the thing they make with their team which are the 21st century skill that the student must be developed. The purpose of this paper is to present the empowerment in oneself to the committee of student association by using the games. All the game follows the empowerment in oneself concept of Kinlaw (1995) which is the student development way that uses the extracurricular activity. The target group is the group of leader student in institute. There are 15 games for all activity in 20 hours and each games can be explained the playing method which the 21st century students can gain the development. The empowerment in oneself, the method which makes these method attendees enable to see their capacity of accomplishment in any activity, is a way which is used for preparing 21st century students to be ready for changing these students from the previous situation which students have only one duty is memorizing from their teachers to be the enthusiastic students, learning by themselves and learning with their team by doing the real thing.